2019
DOI: 10.1044/2019_jslhr-19-00138
|View full text |Cite
|
Sign up to set email alerts
|

Group Experiences and Individual Differences in Stuttering

Abstract: Purpose This study explored group experiences and individual differences in the behaviors, thoughts, and feelings perceived by adults who stutter. Respondents' goals when speaking and prior participation in self-help/support groups were used to predict individual differences in reported behaviors, thoughts, and feelings. Method In this study, 502 adults who stutter completed a survey examining their behaviors, thoughts, and feelings in and around moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 64 publications
2
10
0
2
Order By: Relevance
“…Larger follow-up studies have replicated and expanded these findings. Tichenor and Yaruss (2019a) surveyed 502 adults who stutter to determine what thoughts, feelings, and behaviors they experience during and around moments of stuttering. Results confirmed that speakers alone are privy to the internal sensation of being stuck or out of control when speaking.…”
Section: Understanding the Moment Of Stuttering Itselfmentioning
confidence: 99%
“…Larger follow-up studies have replicated and expanded these findings. Tichenor and Yaruss (2019a) surveyed 502 adults who stutter to determine what thoughts, feelings, and behaviors they experience during and around moments of stuttering. Results confirmed that speakers alone are privy to the internal sensation of being stuck or out of control when speaking.…”
Section: Understanding the Moment Of Stuttering Itselfmentioning
confidence: 99%
“…These "covert" aspects of stuttering are common in persons who stutter. In a survey of persons who stutter, Tichenor and Yaruss (2019a) found that almost 50% of respondents reported that they stuttered covertly at least some of the time-and 10% to 15% reported that they often or always stutter covertly by using coping strategies such as switching words or by avoiding communication altogether. If clinicians view stuttering primarily in terms of observable fluency, there is a risk they might fail to offer treatment simply because they do not witness disfluencies in a person's speech.…”
Section: Fluency Is Not Fully Inclusivementioning
confidence: 99%
“…Irrespective of the viewpoint that one takes about the nature of stuttering and regardless of the age of the speaker, the person who stutters must be a critical contributor to the assessment process, in part because people who stutter may have widely differing experiences (Tichenor & Yaruss, 2019b) and because they will know what goals they seek (Bothe & Richardson, 2011;Sønsterud et al, 2020). They know themselves and their stuttering best; they therefore have important insights about their stuttering that must be taken into account during the analysis of assessment results and in the development of intervention plans.…”
Section: The Importance Of Individualized Assessmentmentioning
confidence: 99%